Pendampingan Penyelarasan Pembelajaran Akuntansi Berbasis SKKNI No. 264 Tahun 2023 pada MGMP Akuntansi Jakarta Timur II - Eneng Sugihyanty; Amor Marundha; Safri Safri (Universitas Dirgantara Marsekal Suryadarma, 2026)
The changing demands of the labor market require accounting education at the secondary school level to be aligned with the latest Indonesian National Work Competency Standards (Standar Kompetensi Kerja Nasional Indonesia—SKKNI). The Accounting Teachers' Working Group (MGMP) of East Jakarta II continues to face challenges in understanding and implementing SKKNI Decree No. 264 of 2023, particularly regarding occupational levels and their integration into classroom instruction. This community service program aimed to enhance teachers' understanding of SKKNI, facilitate consensus on the appropriate occupational level for accounting instruction, and develop recommendations for aligning learning with industry competency standards. The program employed a participatory approach through workshops, focus group discussions (FGDs), and technical mentoring. The results indicate improved teachers' understanding of the SKKNI structure, competency units, competency elements, performance criteria, and occupational level concepts. The program also resulted in an MGMP agreement to adopt Level II as the minimum occupational standard for accounting instruction in vocational high schools and produced recommendations for curriculum alignment, including the integration of SKKNI competency units into teaching materials, the development of competency-based assessments, the incorporation of workplace case studies, and the strengthening of contextual learning practices. Participant evaluations also indicated a high level of satisfaction, with 86.6% rating the speakers' mastery of the subject matter as very good. These outcomes strengthened collaboration between higher education institutions and the MGMP in supporting the implementation of competency-based accounting education that is more closely aligned with the needs of business and industry.